Analisis Perbandingan Metode SMART Dan MOORA Pada Pemilihan Karyawan Terbaik Klinik Kecantikan - Yuris Alkhalifi; Muhammad Rifqi Firdaus; Dinar Ismunandar; Irwan Herliawan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
An employee is a person who works for a particular company or institution. One of the activities that a company or agency often does to motivate its employees to show their best performance is to select the best employees. Making the best employee decisions with simple calculations is often found problematic due to the plethora of considerations of several factors, one of which is the factor that describes how important the assessment weight of one criterion with the business weight of another. The problem was found at Karawang's Nastyaderm Beauty Clinic. Then the solution needed to solve the problem is to use decision-making technology such as the Decision Support System. (SPK). The aim of this research is to find the best employees by using a comparison of two SPK methods namely SMART and MOORA to find out which are the best method rated, easy to apply and relevant. The number of employees that will be evaluated is as many as 5 people. The evaluation was given by the owner of the Beauty Clinic Nastyaderm Karawang, the mother of Dr. Lina Wijaya. The results of research and testing of 5 employees obtained the highest score on the SMART method on behalf of Tiara Anggraeni with a score of 0.725 or 72.5%. By obtaining results from both methods, it provides an overview of the results of the two methods and can help provide alternative solutions to the owner of a beauty clinic to determine the best employee of his working environment